Question
upstudy study bank question image url

i) \( \frac{a^{2}}{c} \times \frac{c^{2}}{a} \) k) \( 3\left(10^{2}\right)^{-2} \) m) \( 2\left(x^{2}\right)^{3} \times 3\left(x^{4}\right)^{-2} \) o) \( \frac{2^{0} \times 2^{1} \times 2^{2}}{2^{-2} \times 2^{-1}} \)

Ask by Montgomery Sullivan. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(i) a · c (k) 3/10000 (m) 6/x² (o) 64

Solution

Let's simplify each expression step by step. ────────────────────────────── (i) Expression: (a²/c) × (c²/a) Step 1: Multiply the numerators and the denominators:   = (a² × c²) / (c × a) Step 2: Combine the like bases by subtracting exponents:   = a^(2-1) × c^(2-1)   = a¹ × c¹   = a · c ────────────────────────────── (k) Expression: 3(10²)⁻² Step 1: Simplify the power inside the parentheses:   (10²)⁻² = 10^(2×(-2)) = 10^(-4) Step 2: Multiply by 3:   = 3 × 10^(-4)   = 3/10⁴   = 3/10000 ────────────────────────────── (m) Expression: 2(x²)³ × 3(x⁴)⁻² Step 1: Simplify each part:   (x²)³ = x^(2×3) = x⁶   (x⁴)⁻² = x^(4×(-2)) = x^(–8) Step 2: Substitute back:   = 2x⁶ × 3x^(–8)   = (2×3) × x^(6–8)   = 6x^(–2) Step 3: Write using positive exponents:   = 6/x² ────────────────────────────── (o) Expression: (2⁰ × 2¹ × 2²) / (2^(–2) × 2^(–1)) Step 1: Combine the exponents in the numerator and denominator by addition:   Numerator exponent: 0 + 1 + 2 = 3, so numerator = 2³.   Denominator exponent: (–2) + (–1) = –3, so denominator = 2^(–3). Step 2: Use the quotient rule (subtract exponents):   = 2^(3 – (–3)) = 2^(3+3) = 2⁶ Step 3: Evaluate 2⁶:   = 64 ────────────────────────────── Summary of Answers: (i) a · c (k) 3/10000 (m) 6/x² (o) 64

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let’s dive into these mathematical expressions! For the first expression \( \frac{a^{2}}{c} \times \frac{c^{2}}{a} \), you can simplify it by canceling out terms. The \( a \) in the denominator and one \( a \) in the numerator cancel out, resulting in \( \frac{ac}{1} = ac \). Now that wasn’t too scary, was it? For \( 3\left(10^{2}\right)^{-2} \), remember that \( (x^m)^{-n} = \frac{1}{x^{mn}} \). So here, you have \( 3 \times \frac{1}{10^{4}} = \frac{3}{10^{4}} = 0.0003 \). It’s a nifty way to express small numbers! Always check to ensure all terms are simplified fully through cancellation before moving forward—it's a common mistake that can trip up even seasoned mathematicians! Plus, having a solid grasp of exponent rules will prevent mistakes in simplifying complex expressions. Keep practicing, and you'll become a pro in no time!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy